El cancel de la Iglesia de San Marcos de León - Morais Vallejo, Emilio (Estudios humanísticos. Geografía, historia y arte, 1999)
In the year 1749 the convent of San Marcos of León decided to build a new lattice gato in the church to separate the presbitery from the main nave; the principal intention was to create a sumptuous work. With this aim, it was made ara iron and bronze grille with barroque characteristics, on a pedestal of colours marble, charged to the architect Blas Suárez Gavilanes and finished by Sancho Menéndez, according to the documentation.